10 CS Learning Model of Sustainable Security Based Management for Thai Microfinance Institutions - Phatnadilok, Sombun; Tupmongkol, Thanatas; Pavapanumkul, Shayut; Woenthong, Somsri; Mahittichatkul, Nasaran; Rachatakulpat, Thanakorn; Kamolyabut, Kanyanont (Chophayom Journal, 2016)
This research objectives were to find out the Learning model of sustainable security based management for Thai Microfinance institutions. The qualitative research design, focus group in Lab Partnership Meeting that use conceptual research framework 7Cs from World Bank and Technical Service Delivery to Microfinance Institutions. From the result of focus group from the four areas and four corners of the Bangkok Metropolitan, such as Minburee, North Bang Khen, South Bangkae and Sathorn etc. Through the result of focus group applied to synthesis learning model for developing of Thai microfinance system in sustainable security, to microfinance institutions by the quantitative research from microfinance institutions customer in the same area and sample size totaling 450 persons by using Taro Yamane Statistical Table and descriptive statistic employed were frequency, percentage, mean, and standard deviation. The finding revealed that: The old learning model 7Cs should be added 3Cs principles was integrated of learning old model were presenting idea of cresitive (creative + positive thinking, care and collateral). The new learning model in terms of integrated of learning both microfinance manager and client. In finding order to meet 10 Cs model for developing of Thai microfinance system management in sustainable security to microfinance were as followings: 1.Cresitive; 2.Client 2 Demand Driven; 3.Context; 4.Change 5.Clearly Defined Results; 6. a Ccountability; 7.Checkability; 8.Cost Effectiveness; 9.Care; and 10. Collateral